A comparison between different chlorophyll content meters under nutrient deficiency conditions. (21st April 2017) - Kalaji, Hazem M.; Dąbrowski, Piotr; Cetner, Magdalena D.; Samborska, Izabela A.; Łukasik, Izabela; Brestic, Marian; Zivcak, Marek; Tomasz, Horaczek; Mojski, Jacek; Kociel, Henryk; Panchal, Balaji M.
ABSTRACT: Chlorophyll content meters have been used successfully to estimate foliar chlorophyll content in various plant species in non-destructive way, especially to study stress physiology and abiotic stresses, such as nutrient deficiency. The main aim of this work was to compare the records of different chlorophyll content meters with the results obtained by the destructive method under the deficiency of main macronutrients in plants growth medium. Four devices (CL-01, SPAD-502, Dualex, and CCM-200) were used to estimate chlorophyll content in maize and tomato plants. In maize plants, all devices validated high accuracy for potassium and nitrogen deficiency and low accuracy for phosphorous and magnesium. In tomato, they showed a high degree of accuracy for calcium, potassium, and iron deficiencies, and low accuracy for phosphorus deficiency. All devices proved to be suitable to provide a reasonably estimation of chlorophyll content under optimal nutrient conditions. However, under nutrient deficiency conditions, tested devices showed different values for the same plant under the same nutrient deficiency. This suggest that, these devices should be validated by a sampling destructive method under such conditions.